TINJAUAN YURIDIS EKSEKUSI DALAM PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN - Sukma Diputra, Dewa Made; Marhaendra Wija Atmadja, Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013, 2013)
Writing a scientific paper entitled "Execution of Judicial Review In The Credit Agreement With Fiduciary guarantee Not Registered ". The method used in this paper is normative. Issues raised in this paper is the execution of the credit agreement with the fiduciary guarantee in the case of debtor violate agreement and how the legal protection of debitor who the fiduciary object is not registered with fiducial guarantee executed by the creditor. From the research, the creditor can not executes fiduciary object if it has not been registered. Before executing the fiduciary object, the creditor must register a credit agreement with fiduciary insurance or may file a suit to the court that the debtor has violates the agreement.
Keywords: Execution of Credit Agreement, Not Registered, Fiducial Guarantee